ANALISIS KEWENANGAN MAHKAMAH KEHORMATAN DEWAN DALAM MENJAGA HARKAT DAN MARTABAT DEWAN PERWAKILAN RAKYAT: Analysis of the Authority of the Honorary Court of the Council in Maintaining the Dignity and Dignity of the House of Representatives - Naila Fitriah Salamah; Sholikul Hadi (Constitution Journal, 2023)
The Council of Honor Court is an instrument of the House of Representatives which aims to uphold and maintain the honor and dignity of the House of Representatives. The formation of the Council's Honorary Court is also considered to increase the credibility of the People's Representative Council. The Honorary Council Council as an instrument has a very important role but has not yet achieved maximum results. This can be seen from several decisions issued by the Council's Honorary Court which are irrelevant so that the decisions made are deemed not to implement the objectives of establishing the Council's Honorary Court. The aim of this research is to analyze and describe the authority of the Council's Honorary Court in maintaining the honor and dignity of the DPR based on the regulations that have been established. The research method used is a normative research method.The results of this research are that the authority of the Council's Honorary Court is explained in the Regulation of the People's Representative Council of the Republic of Indonesia Number 2 of 2015 concerning Procedures for the Council's Honorary Court. In the process of exercising authority it was stated that it was not in accordance with the regulations that had been determined, this was based on the facts and decisions that had been issued by the Council's Honorary Court. The membership structure of the Council's Honorary Court is considered weak, this is based on the membership of the Council's Honorary Court which still consists of only the People's Representative Council, which can give rise to conflict of interest. Abstak Mahkamah Kehormatan Dewan merupakan alat kelengkapan Dewan Perwakilan Rakyat yang memiliki tujuan untuk menegakkan serta menjaga harkat dan martabat Dewan Perwakilan Rakyat. Dibentuknya Mahkamah Kehormatan Dewan juga dianggap dapat meningkatkan kredibilitas Dewan Perwakilan Rakyat. Mahkamah Kehormatan Dewan sebagai alat kelengkapan memiliki peran yang sangat penting namun belum memiliki hasil yang maksimal. Hal demikian dilihat dari beberapa putusan yang dikeluarkan oleh Mahkamah Kehormatan Dewan yang tidak relevan sehingga putusan yang ditetapkan dianggap tidak mengimplementasikan tujuan terbentuknya Mahkamah Kehormatan Dewan. Tujuan dari penelitian ini adalah menganalisis dan mendeskripsikan kewenangan Mahkamah Kehormatan Dewan di dalam menjaga harkat dan martabat DPR berdasarkan peraturan yang telah di tetapkan. Metode penelitian yang digunakan adalah metode penelitian normatif. Hasil penelitian ini adalah Wewenang Mahkamah Kehormatan Dewan dijelaskan dalam Peraturan Dewan Perwakilan Rakyat Republik Indonesia Nomor 2 Tahun 2015 tentang Tata Beracara Mahkamah Kehormatan Dewan. Pada proses pelaksanaan kewenangan dnyatakan tidak sesuai dengan peraturan yang telah ditetapkan hal demikian berdasarkan fakta-fakta dan putusan yang telah dikeluarkan oleh Mahkamah Kehormatan Dewan. Struktur keanggotaan Mahkamah Kehormatan Dewan dianggap lemah hal demikian didasarkan pada keanggotaan Mahkamah Kehormatan Dewan yang masih terdiri dari Dewan Perwakilan Rakyat saja sehingga dapat menimbulkan conflict interest.